REGIONAL POLICY OF SOCIAL INFRASTRUCTURE DEVELOPMENT IN THE CONTEXT OF IMPROVING THE QUALITY OF LIFE OF THE POPULATION OF THE CARPATHIAN REGION OF UKRAINE - Vasyltsiv , Taras; Bil , Mariana; Bachynska Mariіa (Socio-economic relations in the digital society, 2021)
Abstract. The article deals with the basic characteristics of the living standards of population. The work consolidates aspects of the social infrastructure development in a region. The priorities of social infrastructure and peculiarities of its elements performance in Carpathian area are described. It primarily concerns mountainous location of a great number of settlements. Therefore, the specificity of the social infrastructure development in that region involves remoteness of many settlements from administrative and economic centers, problematic access to some services of social and economic character for conformable living. Peculiarities of the social infrastructure development in Carpathian area and their impact of the living standards of population directly depend on climate conditions, particularly weather and natural phenomena. Considering peculiarities of the social infrastructure in Carpathian area, it is determined that organization of social infrastructure in the region has its territorial specificity and should consider the balance and relationship of its elements performance in the system of economic complex of the region; its complex nature should be supported at the state, regional, and local levels; as well as the required number and optimal size of the objects to supply population with social services should be supplied; compliance of the actual conditions and technical equipment with the population’s demands should be provided. The research substantiates directions and tools of the regional policy concerning the social infrastructure development in context of improvement of the population’s living standards, which significantly influence involvement of ecological and social determinants of its improvement, because the primary task of the social infrastructure is to create an appropriate environment for human living that covers such spheres as education, healthcare, culture, sport, residential and public economies. The author of the research identifies expected outcomes from implementation of the instruments of the social infrastructure development in terms of improvement of the living standards of the Carpathian area population in terms of the following areas: effective use of health and recreational potential of the Ukrainian Carpathians; development of cross-border cooperation in the field of improving social infrastructure and environmental protection; transition to smart-oriented development of housing and communal services; improving the transit potential of the Carpathian region; preservation and improvement of the cultural environment. Keywords: social infrastructure, living standards of population, Carpathian area of Ukraine, directions and tools of regional policy, social and ecological determinants. JEL Classification I31, I38, R19, R58 Formulas: 0; fig.: 1; tabl.: 1; bibl.: 10.